UBA1 inhibition contributes radiosensitization of glioblastoma cells via blocking DNA damage repair - Wu, Changyong; Shen, Yang; Shi, Lin; Zhang, Junhao; Guo, Tongxuan; Zhou, Lingni; Wang, Wanzhou; Zhang, Xu; Yu, Rutong; Liu, Xuejiao (Frontiers in Pharmacology, 2023)
Glioblastoma is a brain tumor with high mortality and recurrence rate. Radiotherapy and chemotherapy after surgery are the main treatment options available for GBM. However, patients with glioblastoma have a grave prognosis. The major reason is that most GBM patients are resistant to radiotherapy. UBA1 is considered an attractive potential anti-tumor therapeutic target and a key regulator of DNA double-strand break repair and genome replication in human cells. Therefore, we hypothesized that TAK-243, the first-in-class UBA1 inhibitor, might increase GBM sensitivity to radiation. The combined effect of TAK-243 and radiotherapy on GBM cell proliferation, and colony formation ability was detected using CCK-8, colony formation, and EdU assays. The efficacy of TAK-243 combined with radiotherapy for GBM was further evaluated in vivo, and the mechanism of TAK-243 sensitizing radiotherapy was preliminarily discussed. The results showed that TAK-243, in combination with radiotherapy, significantly inhibited GBM cell proliferation, colony formation, cell cycle arrest in the G2/M phase, and increased the proportion of apoptosis. In addition, UBA1 inhibition by TAK-243 substantially increased the radiation-induced γ-H2AX expression and impaired the recruitment of the downstream effector molecule 53BP1. Therefore, TAK-243 inhibited the radiation-induced DNA double-strand break repair and thus inhibited the growth of GBM cells. Our results provided a new therapeutic strategy for improving the radiation sensitivity of GBM and laid a theoretical foundation and experimental basis for further clinical trials.